أثر التسويق الداخلي في تحقيق التميز التنظيمي في المؤسسات الصغيرة والمتوسطة بمحافظة شقراء-المملكة العربية السعودية - محمد عبد العالم, محمد (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة إلى معرفة أثر التسويق الداخلي، على تحقيق التميز التنظيمي في المؤسسات الصغيرة والمتوسطة، في محافظة شقراء، المملكة العربية السعودية. وقد استخدم الباحث المنهج الوصفي التحليلي للإجابة عن تساؤلات الدراسة، وتم تطبيق الاستبانة كأداة لجمع البيانات من عينة الدراسة، البالغ عددهم 298 مؤسسة، وقد توصلت الدراسة إلى وجود أثر، ذي دلالة إحصائية لأبعاد التسويق الداخلي، على التميز التنظيمي في المؤسسات الصغيرة والمتوسطة، وبناء على تحليل الانحدار الخطي المتعدد، فقد أظهرت النتائج أن أبعاد التسويق الداخلي (تدريب العاملين، تحفيز العاملين، تمكين العاملين) لها تأثير إيجابي على التميز التنظيمي في المؤسسات الصغيرة والمتوسطة. وبينت النتائج –أيضا- أن عنصر تدريب العاملين له التأثير الأكبر على تحقيق التميز التنظيمي. على الرغم من ذلك بينت الدراسة أن عنصري اختيار العاملين والاتصالات الداخلية ليس لها تأثير ذو دلالة إحصائية على التميز التنظيمي. وبناء على النتائج أكدت الدراسة على ضرورة اهتمام صناع القرار في المؤسسات الصغيرة والمتوسطة، بعناصر التسويق الداخلي لتحقيق التميز التنظيمي. وفي ضوء نتائج الدراسة قدم الباحث مجموعة من التوصيات للجهات المعنية. Abstract: The aim of this study is to investigate the influence of internal marketing dimensions on organizational excellence in SMEs in Shaqra governance, Kingdom of Saudi Arabia. The researcher used descriptive analytical methods to answer the study questions, and used a questionnaire for collecting quantitative data from the study sample that consisted of 289 managers. The study findings showed that there was a significant effect of internal marketing dimensions (i.e., Employees’ training, Employees’ motivation, and employees’ empowerment) on organizational excellence in SMEs. Based on the multiple regression analysis applied in the study, results also showed that all dimensions of internal marketing had a significant influence on organizational excellence in SMEs. It also found that Employees’ training had a greater influence on organizational excellence then other dimensions. However, the results show that there is no significant influence of the two dimensions of internal marketing (i.e., Employees’ Selection and internal communication) on organizational excellence. Based on the results, the study concluded that decision makers in SMEs should focus on internal marketing dimensions in SMEs to achieve organizational excellence. In light of the findings, the researcher presented a set of recommendations to the stakeholder.
The Influence of Internal Marketing on Organizational Excellence in Small and Medium Enterprises (SMEs) in the Governorate of Shaqra-Kingdom of Saudi Arabia
مقال
Keywords: التسويق الداخلي ; التميز التنظيمي ; المؤسسات الصغيرة والمتوسطة